A score to predict one-year risk of recurrence after acute ischemic stroke. Issue 5 (July 2021) - Strambo, Davide; Zachariadis, Alexandros; Lambrou, Dimitris; Schwarz, Ghil; Sirimarco, Gaia; Aarnio, Karolinaa; Putaala, Jukka; Ntaios, George; Vemmos, Kostantinos; Michel, Patrik
Background: An acute ischemic stroke carries a substantial risk of further recurrences. We aimed at developing and validating a prognostic tool to predict one-year stroke recurrence after acute ischemic stroke. Methods: An integer score was derived by Cox regression analysis on a hospital-referred cohort of 3246 acute ischemic stroke patients from Switzerland, and tested for external validity in three similar independent cohorts from Athens ( n  = 2495), Milan ( n  = 1279), and Helsinki ( n  = 714) by means of calibration and discrimination. Results: In the derivation cohort, the recurrence rate was 7% ( n  = 228/3246). We developed a nine-point score comprising: previous stroke or transient ischemic attack (1-point), stroke mechanism (small vessel disease and unknown mechanism: 0-points; rare stroke mechanism: 3-points; other mechanisms: 1-point), pre-stroke antiplatelets (1-point), active malignancy (2-points), chronic cerebrovascular lesions on imaging (1-point) and absence of early ischemic changes on first imaging (1-point). In the derivation cohort, the one-year risk of re-stroke was 3.0% (95%CI 1.9–4.1) in 932 (29%) patients with a score 0–1, 7.2% (6.1–8.3) in 2038 (63%) with a score 2–4, and 19.2% (14.6–23.9) in 276 (8%) with a score ≥ 5. The score calibrated well in the Athens (recurrences = 208/2495), but not in the Helsinki (recurrences = 15/714) or Milan (recurrences = 65/1279) cohorts. The AUC was 0.67 in the derivation cohort, and 0.56, 0.70, and 0.63 in the Athens, Helsinki, and Milan cohorts, respectively. Conclusion: We developed a score to predict one-year stroke recurrence risk in patients with acute ischemic stroke. Since the score was not completely validated when applied to external datasets where it displayed poor to fair calibration and discrimination, additional efforts are required to ameliorate our accuracy for predicting stroke recurrence, by better refining this prognostic tool or developing new ones. Clinical and radiological markers of established cerebrovascular disease and stroke etiology were better predictors than the usual demographic vascular risk factors.